#TITLE_ALTERNATIVE# - Salsabila (NIM : 201 95 507), Ellis
Abstrak: We consider the following second order nonlinear differential inequalities uLu0,to where the operator L is given by : Lu = u + a(t)f(u), the function a e C[0,oo) is not necessarily nonnegative and the function f E Cl(0,oo) satisfies uf(u) > 0, fu) > 0 V u =O. Oscillation criteria for the above differential inequalities will be established by modification of the method that has been used previously for the above differential inequalities and differential equation Lu = O. The above differential inequalities is called oscillatory in [0,00) if every solution of the differential inequalities is oscillatory in [0,co) and a solution u(t) of the above differential inequalities is called oscillatory in [0,00) if for every t 0, there exists a to t such that u(to) = O. The results obtained will contain and improve the previous results for the above inequalities, and extended oscillation criteria for differential equation Lu = 0 to the above differential inequalities.